PROBLEMS OF FORMING TOLERANT RELATIONSHIPS OF PUPILS AT PRIMARY SCHOOL WITHIN INCLUSIVE EDUCATION - Тасова, К.Ж. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The article discusses the problem of involving people with disabilities in the life of society, the problem of their adaptation and socialization. Development of a tolerant attitude of children towards children with disabilities in primary school.
Keywords: inclusive education; tolerance; relationships; adaptation; children with limited capabilities; primary school; interaction